A Novel DTFC Based Efficiency and Dynamic Performance Improvement of IPMSM Drive - Rahman, Md. Mizanur (My University, 2016)
With the advancements in magnetic materials and semiconductor technology, permanent magnet synchronous motor (PMSM) is becoming more and more popular in high power industrial applications due to its high energy density, high power factor, low noise and high efficiency as compared to conventional AC motors. Field oriented vector control (VC) and direct torque and flux control (DTFC) are used for high performance drives. Among these two techniques DTFC is faster and simpler than that of conventional VC scheme as DTFC scheme doesn’t need any coordinate transformation, pulse width modulation and current regulators. The DTFC based motor drives utilizes hysteresis band comparators for both torque and flux controls. Both torque and flux are controlled simultaneously by the selection of appropriate voltage vectors from the inverter. However, DTFC suffers from high torque ripples due to discrete nature of control system and limited voltage vectors from the inverter. Torque ripples can be minimized by increasing the sector numbers of the DTFC scheme which increases the switching frequency of the inverter. Traditionally, researchers chose a constant value of reference air-gap flux to make the control task easy but it is not acceptable for high performance drives as the air-gap flux changes with the operating conditions and system disturbances. Furthermore, if the reference air-gap flux is maintained constant, it is not possible to control the motor over the wide speed range operation. Moreover, conventional six-sector based DTFC scheme suffers from high torque ripples, which is the major drawbacks to achieve high dynamic performance. Therefore, this thesis presents a novel eighteen-sector based DTFC scheme to achieve high dynamic performance with minimum torque ripples. In addition, the loss minimization algorithm (LMA) is incorporated with proposed DTFC scheme in order to improve the efficiency while maintaining high dynamic performance. This thesis further presents modified eighteen-sector based DTFC scheme to overcome the unbalanced voltage effects in any sector of conventional six-sector based system to improve the dynamic performance of the proposed system. This thesis also presents a novel sector determination algorithm to determine the sector number of the stator flux linkage vector which reduces the computational burden to the microprocessor. A five level torque hysteresis comparator based DTFC scheme is also proposed to reduce the torque ripple. Further, a backstepping based nonlinear controller is developed for IPMSM drive that achieves the lowest possible torque ripples in steady state. In this controller development, the control variable is motor electromagnetic developed torque and stator air-gap flux linkages similar to classical DTFC but the errors are forced to zero using backstepping process to get better dynamic performance. The effectiveness of the proposed systems is verified through the development of a simulation model using Matlab/Simulink. Performance of the proposed nonlinear controller is investigated extensively at different operating conditions such as sudden speed and load changes. Then the complete IPMSM drives, incorporating the proposed LMA and eighteen-sector based DTFC scheme and nonlinear controller with torque and flux as virtual control variables are successfully implemented in real-time using digital signal processor (DSP) board-DS1104 board for laboratory 5-hp motor. The effectiveness of the proposed control techniques are verified in both simulation and experiment at different operating conditions. It is found that, the nonlinear controller based IPMSM drive provides the best performance in terms of torque ripple among all the DTFC scheme developed in the thesis. The results show the robustness of the drive and it’s potentiality to apply for real-time industrial drive applications.
Keywords: Permanent magnet synchronous motor; Field oriented vector control; Direct torque and flux control; Voltage source inverter; Nonlinear controller